Post-Islamism: The New Face of Political Islam in Indonesia - Huda, Muchammad Nur (http://jagadalimussirry.com/, 2021)
Abstract. Movement of Islamic politics in post- Islamism is movement ideology in the discourse of contemporary Islamic studies in Indonesia are being crowded discussed. Post-Islamism first time emerged as the faces of Islam political supporters of the ideology of Islamism in contensasi election of the general governor of Jakarta in 2017 through action to defend Islam on 2nd December 2016 or what is known as the 212 movement. This article aims to examine in detail the emergence of post-Islamism as the new face of political Islam in Indonesia and how post-Islamism is built into a